Brand Identity Model to Develop Bondowoso Regency as the "Republic of Coffee" in Indonesia - Junaedi, Rusli Akhmad; Riswandari, Ninuk; Faris, Faris (Jurnal Media dan Komunikasi Indonesia, 2025)
The development of regional brand identity is crucial in enhancing economic competitiveness and strengthening the image of Bondowoso Regency as a leading coffee center. Bondowoso Regency, as a historic site and coffee production hub, faces challenges in maintaining and expanding its positive image to support sustainable economic growth and promote culture-based tourism, as well as its natural resource potential. This study proposes a brand identity model based on Kapferer’s Brand Identity Prism theory and empirical data to establish Bondowoso Regency's branding as the "Republic of Coffee" in addressing these challenges. A qualitative approach was employed in data collection, involving interviews with eight informants from various stakeholders, field observations, and documentation from both primary and secondary sources. Validation was carried out through data triangulation and documentation analysis to ensure the consistency and validity of the findings. Data analysis integrated theory and empirical data in developing a strategy for building an authentic, integral, and sustainable brand identity. The research findings indicate that the success of this branding can enhance the region’s image, attract tourists, and drive economic growth through strong and consistent brand identity elements. These findings underscore the importance of collaboration among the government, community, and businesses in establishing a relevant and enduring brand image. The implementation of this model is expected to position Bondowoso Regency as a national and international hub for coffee.